Synthesis, characterization and thermal behaviour on solid pyruvates of light trivalent lanthanides - Siqueira,A. B. (2007)
Solid State Ln-L compounds, where Ln stands for light trivalent lanthanides (La - Gd) and L is pyruvate, have been synthesized. Thermogravimetry and derivative thermogravimetry (TG/DTG), differential scanning calorimetry (DSC), X-Ray powder diffractometry, infrared spectroscopy, elemental analysis, and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, ligand denticity, thermal behaviour and thermal decomposition of the isolated compounds.